Relationship of Saphenous Magna Vein Diameter to Venous Occlusion & Revised Venous Clinical Severity Score (rVCSS) in Patients with Chronic Venous Insufficiency (IVK) Post-Endovenous Microwave Ablation (EMA) - Rachmanto, Ary; Patrianef, Patrianef; Kekalih, Aria (Jurnal Locus Penelitian dan Pengabdian, 2025)
Chronic venous insufficiency (IVK) is characterized by impaired reverse blood flow in the lower extremities. Endovenous microwave ablation (EMA) is a minimally invasive procedure with advantages on large diameter veins. This study aimed to determine the relationship between the diameter of the great saphenous vein (GSV) and venous occlusion in the first week and the change in the Revised Venous Clinical Severity Score (rVCSS) in the first month post-EMA. This retrospective cohort design study involved 47 patients from RSCM, Hermina Bekasi Hospital and Hermina Depok Hospital for the January-December 2024 period. Data collection used medical record tracing, GSV diamter, GSV venous occlusion, rVCSS score. Bivariate analysis with Chi-Square or Fischer Test, multivariate analysis with multiple logistic regression while diagnostic parameter analysis with ROC curve. The venous occlusion rate reached 87.2%, and the change in rVCSS score was 63.8%. There was a significant relationship between GSV diameter and GSV occlusion [p<0.001; MD -2.101 (95% CI: -2.84; -1.36)] and with changes in rVCSS score [B=1.188; p=0.029; OR 3.28 (95% CI: 1.13–9.53)]. The GSV diameter threshold value of 6.55 mm was a good predictor of occlusion (75.6% sensitivity, 100% specificity), but not good for rVCSS change (70% sensitivity, 52.9% specificity). Other factors such as gender, age ?60 years, hypertension, diabetes, and obesity were not significantly related. GSV diameter was significantly associated with venous occlusion and changes in rVCSS scores post-EMA. A cut-off value of 6.55 mm can be a good predictor of occlusion.